2010
DOI: 10.1007/s11105-009-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an AGAMOUS Homolog from Fraxinus pennsylvanica

Abstract: An AGAMOUS homolog (FpAG) was isolated from green ash (Fraxinus pennsylvanica) using a reverse transcriptase polymerase chain reaction method. Southern blot analysis indicated that FpAG was present as a singlecopy sequence in the genome of green ash. RNA accumulated in the reproductive tissues (female inflorescence, male inflorescence, and fruit) and vegetative tissues (leaves and in vitro-germinated seedlings). Expression was higher in reproductive tissues than in vegetative tissues. Ectopic expression of FpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…As well as changes in the development of reproductive organs, strong phenotype plants of 35S::PaAG - 1 tobacco also displayed changes in vegetative growth, notably small curled leaves and reduced plant stature. The literature reports that transgenic Arabidopsis plants overexpressing functional AG orthologues show similar vegetative growth defects [12], [13], [35], [36]. Thus, the results of functional analyses in the tobacco host are consistent with the conclusion that PaAG is a floral homeotic C function gene.…”
Section: Discussionsupporting
confidence: 84%
“…As well as changes in the development of reproductive organs, strong phenotype plants of 35S::PaAG - 1 tobacco also displayed changes in vegetative growth, notably small curled leaves and reduced plant stature. The literature reports that transgenic Arabidopsis plants overexpressing functional AG orthologues show similar vegetative growth defects [12], [13], [35], [36]. Thus, the results of functional analyses in the tobacco host are consistent with the conclusion that PaAG is a floral homeotic C function gene.…”
Section: Discussionsupporting
confidence: 84%
“…a hybridized with sense probe; b PmAG showed expression in the pollen, anthers, and carpel, but not in the corolla. se, sepal; pe, petal; st, stamen; po, pollen (Rutledge et al 1998;Du and Pijut 2010). The exhibited phenotypes of the transgenic plants were normal, except for a change in petal color.…”
Section: Discussionmentioning
confidence: 99%
“…An alignment of the deduced CsMADS24 protein sequence with that of other AG orthologs from different plant species in literature references was performed by Clustal Omega. The results showed that CsMADS24 was well aligned with the sequences and shared 60.18, 61.54, 63.01, 63.60, 63.98, 64.91, 68.84, 69.01, 70.61, and 71.49% identities with the AG orthologs LLAG1 [11], AtAG [9], OsMADS3 [33], FpAG [12], FaesAG [25], FnAG [18], HpAG [13], MAwuAG [14], PsAG [34], and PrseAG [15], respectively (Fig. 2).…”
Section: Multiple Sequence Alignment and Phylogenetic Analysis Of Csmmentioning
confidence: 87%
“…Overexpression of AG induces a conversion of sepals into carpels and petals into stamens in the flower [9]. To date, the AG orthologs have been identified and characterized from a diverse number of plant species, such as Lilium longiflorum [11], Fraxinus pennsylvanica [12], Hosta plantaginea [13], Magnolia wufengensis [14], Prunus lannesiana [15], Magnolia stellata [16], Carya illinoinensis [17] and Fraxinus nigra [18]. Arabidopsis plants with ectopic expression of AG orthologs from these plants also displayed homeotic changes.…”
Section: Introductionmentioning
confidence: 99%